Toward SDG 3 in a developing nation: the role of health expenditure, financial development, and population growth in shaping health outcomes - Xiang, Xiaohan; He, Shengwei; Abid, Aysha (Frontiers in Public Health, 2025)
This study examines how macroeconomic and demographic factors influence public health outcomes in Bangladesh from 2000 to 2022, using the Autoregressive Distributed Lag (ARDL) approach and the associated Error Correction Mechanism (ECM). The estimated coefficients represent marginal effects, which indicate the absolute change in each health indicator for a one-unit change in the explanatory variables, holding other factors constant. The analysis focuses on three health indicators: life expectancy at birth, infant mortality rate, and under-five mortality rate, and four explanatory variables: public health expenditure, GDP per capita, domestic credit to the private sector, and population growth rate. Results show a stable long-run relationship among the variables. Higher public health expenditure, GDP per capita, and financial development are generally associated with improved health outcomes, while rapid population growth is linked to poorer child health. The ECM results indicate that when short-term fluctuations occur, health outcomes gradually return to their long-term path. The Error Correction Term (ECT) measures the speed of this adjustment and shows how quickly equilibrium is restored after a disruption. These findings suggest that while economic growth and financial development can support better health outcomes, their impact depends on managing demographic pressures and improving the efficiency of health spending. Coordinated fiscal, financial, and population policies are essential to sustain health gains and advance Bangladesh’s progress toward Sustainable Development Goal 3 (SDG 3).